2016
DOI: 10.1016/j.apmr.2015.08.434
|View full text |Cite
|
Sign up to set email alerts
|

Site-Specific Transmission of a Floor-Based, High-Frequency, Low-Magnitude Vibration Stimulus in Children With Spastic Cerebral Palsy

Abstract: Objective To determine the degree to which a high-frequency, low-magnitude vibration (HLV) signal emitted by a floor-based platform transmits to the distal tibia and distal femur of children with spastic cerebral palsy (CP) during standing. Design Cross-sectional study Setting University research laboratory Participants 4 to 12 year-old children with spastic CP who could stand independently (n=18) and typically developing children (n=10) participated in the study. Intervention Not applicable Main out… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 34 publications
(45 reference statements)
0
4
0
Order By: Relevance
“…This may have been due to the different vibration intensities received by the different body parts. There was evidence in a study that there is an enhanced transmission of floor-based vibration at the distal tibia but a reduction at the distal femur [ 38 ]. Similarly, a previous report demonstrated significantly increased lower-limb lean mass and total body bone mineral content after a 20-week WBVT program using an identical WBVT plate from the same manufacturer of the plate used in the former study ( n = 40) [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…This may have been due to the different vibration intensities received by the different body parts. There was evidence in a study that there is an enhanced transmission of floor-based vibration at the distal tibia but a reduction at the distal femur [ 38 ]. Similarly, a previous report demonstrated significantly increased lower-limb lean mass and total body bone mineral content after a 20-week WBVT program using an identical WBVT plate from the same manufacturer of the plate used in the former study ( n = 40) [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…This technique uses the bone’s response to low-frequency vibration generated by a mechanical shaker through a probe placed on the participant’s skin [ 32 ]. Since vibration transmission is site-specific and can be attenuated differentially based on body biomechanics or composition [ 63 ], mechanical response tissue analyzer output cannot be compared with the DXA technique. The third method of measurement addressed in this review is quantitative ultrasound used by Chen et al [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…The definition of vibration exposure varies between single 30 33 and repetitive bouts of vibration. 15 , 34 – 37 The duration of the applied vibration varies: 3, 15 10, 37 and 30 seconds 31 , 33 and 1, 32 , 34 , 36 3, 30 and 10 minutes. 35 Details of vibration application can be found in Table 3 .…”
Section: Resultsmentioning
confidence: 99%
“…The majority of the studies cited (21) were executed in subjects aged 3–17 years. Seven cross-sectional experiments 15 , 30 , 31 , 33 , 35 , 37 , 38 and 14 longitudinal trials 46 , 50 60 , 63 , 64 elaborated the efficiency of VT in children, whereas only three 32 , 34 , 36 cross-sectional and four 36 , 47 49 longitudinal studies included adult volunteers older than 17 years. In the last few decades, scientific debate in the field of neurorehabilitation has consistently concluded that training regimes commonly achieve higher efficiency in children compared to adolescent patient groups.…”
Section: Resultsmentioning
confidence: 99%